Exploring Music-Based Rehabilitation for Parkinsonism through Embodied Cognitive Science - Schiavio, Andrea; Altenmüller, Eckart (Frontiers in Neurology, 2015)
Recent embodied approaches in cognitive sciences emphasise the constitutive roles of bodies and environment in driving cognitive processes. Cognition is thus seen as a distributed system based on the continuous interaction of bodies, brains, and environment. These categories, moreover, do not relate only causally, through a sequential input-output network of computations; rather, they are dynamically enfolded in each other, being mutually implemented by the concrete patterns of actions adopted by the cognitive system. However, while this claim has been widely discussed across various disciplines, its relevance and potential beneficial applications for music therapy remain largely unexplored. With this in mind, we provide here an overview of the embodied approaches to cognition, discussing their main tenets through the lenses of music therapy. In doing so we question established methodological and theoretical paradigms and identify possible novel strategies for intervention. In particular, we refer to the music-based rehabilitative protocols adopted for Parkinson’s Disease (PD) patients. Indeed, in this context it has recently been observed that music therapy not only affects movement-related skills but that it also contributes to stabilising physiological functions and improving socio-affective behaviours. We argue that these phenomena involve previously unconsidered aspects of cognition and (motor) behaviour, which are rooted in the action-perception cycle characterising the whole living system.